COMPARATIVE STUDIES OF THE IDEAS OF RATIONALITY IN THE PHILOSOPHICAL THOUGHT OF EARLY MODERN EUROPE - Ruzmatova Gulnoz Mirakhrarovna (European Journal of Humanities and Educational Advancements, 2024)
Scholars in the realm of social knowledge are increasingly focusing on examining the philosophical legacies and valuable spiritual contributions crafted by both Western and Eastern intellectuals. Consequently, it is imperative for us to familiarize ourselves with the seminal works of contemporary philosophical thought. This approach is essential for a precise and unbiased evaluation of the evolution of philosophical concepts, the intellectual progress within our own society, and the primary concerns of modern philosophy. Hence, the exploration of philosophical issues and heritage consistently remains a pressing matter on the scholarly agenda